(untitled) (Marketing Journal, 2025)
The article examines the issues of assessing international competitiveness and its methodological foundations. A comparative analysis of major international indices is conducted, including the Global Competitiveness Index (GCI) developed by the World Econo mic Forum, the World Competitiveness Yearbook (IMD), and the Competitive Industrial Performance Index (CIP) introduced by UNIDO. These indices highlight the key drivers of competitiveness such as macroeconomic stability, infrastructure, 146 education, technological advancement, and industrial performance. The study emphasizes the importance of applying these methodological approaches in enhancing national competitiveness and aligning with global economic development trends.